Antisaccades in Parkinson disease: A new marker of postural control?. (28th February 2017) - Ewenczyk, Claire; Mesmoudi, Salma; Gallea, Cécile; Welter, Marie-Laure; Gaymard, Bertrand; Demain, Adèle; Yahia Cherif, Lydia; Degos, Bertrand; Benali, Habib; Pouget, Pierre; Poupon, Cyril; Lehericy, Stéphane; et al.
Abstract : Objective: To describe the relation between gaze and posture/gait control in Parkinson disease (PD) and to determine the role of the mesencephalic locomotor region (MLR) and cortex-MLR connection in saccadic behavior because this structure is a major area involved in both gait/postural control and gaze control networks. Methods: We recruited 30 patients with PD with or without altered postural control and 25 age-matched healthy controls (HCs). We assessed gait, balance, and neuropsychological status and separately recorded gait initiation and eye movements (visually guided saccades and volitional antisaccades). We identified correlations between the clinical and physiologic parameters that best characterized patients with postural instability. We measured resting-state functional connectivity in 2 pathways involving the frontal oculomotor cortices and the MLR and sought correlations with saccadic behavior. Results: Patients with PD with postural instability showed altered antisaccade latencies that correlated with the stand-walk-sit time ( r = 0.78, p < 0.001) and the duration of anticipatory postural adjustments before gait initiation ( r = 0.61, p = 0.001). Functional connectivity between the pedunculopontine nucleus (PPN) and the frontal eye field correlated with antisaccade latency in the HCs ( r = −0.54, p = 0.02) but not in patients with PD. Conclusions: In PD, impairment of antisaccade latencies, a simple and robust parameter, may be an indirect marker correlated with impaired release of anticipatory postural program. PPN alterations may account for both antisaccade and postural impairments.